1988
DOI: 10.1002/path.1711540407
|View full text |Cite
|
Sign up to set email alerts
|

Flash labelling of S‐phase cells in short‐term organ culture of normal and pathological human endometrium using bromodeoxyuridine and tritiated thymidine

Abstract: Normal hyperplastic and malignant endometrial specimens were labelled in vitro with bromodeoxyuridine (BrdU). S-phase cells were stained after DNA denaturation, using a monoclonal antibody to BrdU and an indirect immunoperoxidase method. Various conditions for BrdU uptake, DNA denaturation, and staining were tested. BrdU labelling was compared with autoradiography using tritiated thymidine, with good correlation. Glandular labelling indices of proliferative endometrium were significantly higher than both secre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1989
1989
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…BrdU labeling is comparable to [ 3 H]thymidine for analysis of LI, and use of this nonradioactive thymidine analogue has made it possible to study LI in vivo in large mammals, including primates [6,11,31,32]. The effect of estrogen on endometrial LI was readily apparent.…”
Section: Discussionmentioning
confidence: 97%
“…BrdU labeling is comparable to [ 3 H]thymidine for analysis of LI, and use of this nonradioactive thymidine analogue has made it possible to study LI in vivo in large mammals, including primates [6,11,31,32]. The effect of estrogen on endometrial LI was readily apparent.…”
Section: Discussionmentioning
confidence: 97%
“…This immunohistochemical method allows measurement of the SPF without the need for autoradiography or radioisotopes and has been shown to give similar results to 3 HTdR labelling [17]. Further work by Meyer and colleagues found BrdU labelling of breast cancer specimens to correlate with S-phase measured by 3 HTdR [18] and flow cytometry [14].…”
Section: S-phasementioning
confidence: 99%
“…Early studies showed that BrdU is as accurate as [3H]-T in providing estimates of S-phase fractions in labeling-index assays and by bivariate flow cytomeuy (3)(4)(5)(6)(7)10,19). Other investigators measured [3H]-T and BrdU incorporation simultaneously and found that the same cells develop positively for both precursor analogues (5,6,(20)(21)(22)(23). To our knowledge, the present work is the first in which DNA content as well as BrdU and [3H]-T incorporation has been measured for the same cells.…”
Section: Discussionmentioning
confidence: 50%